Effect of Qualea multiflora on Macrophages and Tumour Cells - Carli, Camila B. de A. [UNESP]; Quilles, Marcela B. [UNESP]; Vilegas, Wagner [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Colegio Farmaceuticos Provincia de Buenos Aires, 2013)
Species of the genus Qualea are used by the Brazilian people as a natural anti-inflammatory. Based on this evidence, we evaluated the effects of terpene fractions beta F and TF (rich in beta-sitosterol and terpenoids, respectively) obtained from Qualea multiflora on nitric oxide production, cytokines (IL-1, IL-10, IL-12, and TNF-alpha) and the transcription factor NF-kappa B by peritoneal macrophages. Since there is a relationship between inflammation and cancer, the cytotoxicity of beta F and TF against mammary and pulmonary tumoural cell lineages, and macrophages was evaluated. Inhibition levels close to 90% of the production of NO, IL-1, IL-12 and TNF-alpha; about 32% of NF-kappa B; and a large stimulation of IL-10 production (close to the positive control) by peritoneal macrophages were observed in response to beta F and TF which are correlated with anti-inflammatory activity. Additionally, the samples showed cytotoxic activity against tumoural cells but not against macrophages. Since anti-inflammatory activity is important in tumour inhibition, further examination of potential anti-cancerous activity of Qualea multiflora is warranted.
Keywords: Cancer; Macrophages; Qualea multiflora